PENGARUH KEPEMILIKAN MANAJERIAL TERHADAP HUBUNGAN PERENCANAAN PAJAK, PROFITABILITAS, DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA (STUDI PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BEI TAHUN 2017-2019) - Erin Yuniar; Maslichah Maslichah; Dwiyani Sudaryanti (Universitas Islam Malang, 2021)
The purpose of this study was to see whether there is an effect of managerial ownership on tax planning, profitability and deferred tax expense on earnings management. The population of this research is food and beverage companies listed on the IDX in 2017-2019. The sampling technique used purposive sampling and found 15 companies that match the criteria. The data analysis method used is multiple linear regression analysis and moderated regression analysis. The results of deferred research show that managerial owners are not able to moderate the relationship between tax planning, profitability, and deferred tax expense on earnings management. Keywords : Managerial Ownership, Tax Planning, Profitability, Deferred Tax Expense, Earnings Management